Building Life-cycle Management. Information Systems and Technologies Selected Papers - Ginzburg, Alexander; Galina, Kashevarova; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers the latest advances, innovations, and applications in the field of information systems and construction engineering, as presented by researchers and engineers at the International Scientific Conference Building Life-cycle Management. Information Systems and Technologies, held in Moscow, Russia on November 26, 2021. It covers highly diverse topics, including Information modeling technologies in building life-cycle management, Mathematical models and methods for building life-cycle management, Management of organizational processes in construction. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations in the construction industry.
Chapter 1: Industry 4.0 Technologies for Ensuring the Func-tionality of Urban Infrastructure Socially Significant Elements: a Review -- Chapter 2: BIM-technologies in Digital Modelling of the City Water Utility Operation -- Chapter 3: Theoretical Basis of the Development and the Possibility of Monitoring Systems Design Automation for Load-bearing Structures -- Chapter 4: Automated Information System for Monitoring Technical Condition During Operation of Production Buildings -- Chapter 5: Information Support of Integrated Security for Capital Construction Projects -- Chapter 6: Organizational-technological Genesis as the Basis for Information Modeling of the Building Systems Changes -- Chapter 7: Additive Manufacturing Based on Building Information Model Data -- Chapter 8: Predicting the Elements Operation of Buildings$1 (BEngineering Equipment Using the Big Data Analysis Technologies -- Chapter 9: About the Distortion Model of Operational Compressed-Bent Bars with Induced Anisotropy.s
Keywords: Construction industry -- Management; Environmental engineering; Civil engineering; Environmental management; Industrial Management; Construction Management; Environmental Civil Engineering; Environmental Management; Industrial Management; Civil engineering -- Congresses; Life cycle costing -- Congresses; Life cycle costing